Influence of Sleep Stage on the Determination of Positional Dependency in Patients With Obstructive Sleep Apnea - Ryu, Somi; Kim, Seung Chan; Kim, Rock Bum; Lee, Byeong Min; Park, Sang-Wook; Jeon, Yung-Jin; Joo, Yeon-Hee; Cho, Hyun-Jin; Kim, Sang-Wook (Clinical and experimental otorhinolaryngology, 2024)
Objectives. The supine sleep position and the rapid eye movement (REM) stage are widely recognized to exacerbate the severity of obstructive sleep apnea (OSA). Position-dependent OSA is generally characterized by an apnea-hypopnea index (AHI) that is at least twice as high in the supine position compared to other sleep positions. However, this condition can be misdiagnosed if a particular sleep stage—REM or non-REM (NREM)—predominates in a specific position. We explored the impact of the sleep stage on positional dependency in OSA.Methods. Polysomnographic data were retrospectively analyzed from 111 patients with OSA aged 18 years or older, all of whom had an AHI exceeding five events per hour and slept in both supine and non-supine positions for at least 5% of the total sleep time. The overall ratio of non-supine AHI to supine AHI (NS/S-AHI ratio) was compared between total, REM, and NREM sleep. Additionally, a weighted NS/S-AHI ratio, reflecting the proportion of time spent in each sleep stage, was calculated and compared to the original ratio.Results. The mean NS/S-AHI ratio was consistent between the entire sleep period and the specific sleep stages. However, the NS/S-AHI ratios for individual patients displayed poor agreement between total sleep and the specific stages. Additionally, the weighted NS/S-AHI ratio displayed poor agreement with the original NS/S-AHI ratio, primarily due to discrepancies in patients with mild to moderate OSA.Conclusion. The weighted NS/S-AHI ratio may help precisely assess positional dependency.